Western diets, gut dysbiosis, and metabolic diseases: Are they linked?. (4th March 2017) - Martinez, Kristina B.; Leone, Vanessa; Chang, Eugene B.
ABSTRACT: Obesity afflicts 36.5% of the US population and 600 million individuals world-wide. Thus, it is imperative to understand the risk factors underlying metabolic disease including diet, activity level, sleep, and genetics. Another key contributory factor is the gut microbiota given its widely reported role in the development of metabolic disease. The gut microbiota, particularly its structure and function, is heavily influenced by Western style diets rich in a complex mixture of fats and high in simple sugars. In this review, the profound impact of obesity and Western diets on the gut microbiota will be illustrated, and the following research questions will be addressed: 1) to what extent do high fat diets (HFDs) alter community membership and function and does this depend upon the amount or type of fat consumed?, 2) how rapidly do dietary shifts alter gut microbial communities?, 3) are these alterations sustained or can the microbiome recover from dietary stress?, 4) how does diet drive host-microbe interactions leading to obesity?, and 5) what can be done to restore the detrimental impact of HFD on the gut microbiota? The goal of this review is to address these questions by parsing out the effects and underlying mechanisms of how Western diets impact the gut microbiota and host. By doing so, potential avenues for further exploration and strategies for microbiome-based interventions to prevent or treat diet-induced obesity may become more apparent.